Revisão bibliométrica sobre o uso da análise de variância e de sobrevivência em estudos de germinação de sementes - Roesler, Gustavo Dutra (Universidade Federal de São Carlos, 2021)
Scientific studies with seeds are developed for a wide range of purposes, and statistical analysis of data is an essential component for reliability and experimental proof. Among the statistical methods adopted, the analysis of variance followed by the application of means tests presents itself as the main tool, however, due to the characteristics of the seed data, other methods can be applied, among which is the survival analysis. Therefore, this work aimed to verify, based on a bibliometric analysis, the use of analysis of variance and survival analysis in studies with seed germination and to examine the applications of survival analysis in original articles from the database Web of Science, for the period 2000 to 2020. The search strategy consisted of indexing terms for each type of statistical analysis (analysis of variance and survival analysis) by boolean and truncation operators, restricting the search to original articles. In the study were evaluated quantitatively the relationships of publications between areas of knowledge, annual evolution of scientific production, countries and journals in which the articles were published and research institutions responsible for carrying out the studies and, qualitatively, the general application in studies of germination, emergence and/or vigor. Furthermore, the publications were also classified according to the themes and potential for applying survival analysis in studies in seed science: Physiological Studies, Plant Ecology, Seed Dispersion, Weed Management and Methodological Propositions. It was observed that the application of the analysis of variance was 9 times higher compared to the survival analysis for the analyzed period, with emphasis on articles linked to journals or researchers in Brazil (46.70%). As for the analysis of survival, the USA was the country with the highest productivity in publications (40.63%), with research mainly related to studies in Plant Ecology and Physiology. As for the applicability of the survival analysis were verified, with higher frequency, tests involving the evaluation of factors influencing dormancy, physiological stresses, dispersal capacity, population differences and developmental habitats that affected, to a greater or lesser extent, seed germination.
Bibliometric review on the use of analysis of variance and survival analysis in seed germination studies
Keywords: Agricultura; ANOVA; Bibliometria; Dados censurados; Tempo de falha; Agriculture; Bibliometrics; Censored data; Failure time; CIENCIAS AGRARIAS::AGRONOMIA